Evaluation of the Quality of Healthcare Services for the ElderlyAt the Kakaskasen Public Health Center based on MINISTRY OF HEALTH REGULATION STANDARDS NUMBER 67 OF 2015 - Gita Mait; Jonesius Eden Manoppo; Christian Bertom Pajung; Jilly Toar; Vera Tombokan; Maxie M. Moleong (International Journal of Health Engineering and Technology, 2026)
This aim of this study to evaluate the quality of elderly care at the Kakaskasen Public Health Center, referring to the standards of the Indonesian Ministry of Health Regulation Number 67 of 2015. The background of this research is based on the increasing population in Indonesia, which demands more friendly, integrated, and customized healthcare services for the elderly. Theresearch method used is a descriptive qualitative approach with data collection techniques including interviews, observation, and documentation. The research subjects include the head of the community health center, healthcare workers, and the elderly as service users. The research results show that in terms of human resources, healthcare personal are already adequate and have received specialized geriatric training to enchance their competence in managing elderly health . The service facilities and infrastructure are quite good, but there are still limitations in diagnostic facilities and comfort aspects. From the service provider's perspective, promotional, preventive, curative, and rehabilitative activities have been carried out according to standards, but the waiting time is still relatively long and is a major obstacle. Overall, the quality of elderly healthcare services at the Kakaskasen Community Health Center can be categorized as meeting most of the standards set by the Minister of Health Regulation No. 67 of 2015, but improvements are still needed in several aspects, particularly in the competence of healthcare workers, facilities and infrastructure, and the efficiency of service time.